Origin of Podiform Chromitites in the Sebuku Island Ophiolite (South Kalimantan, Indonesia): Constraints from Chromite Composition and PGE Mineralogy - Idrus, Arifudin (MDPI, 2022)
The presence of PGM associated with the podiform chromitites in the Jurassic–Cretaceous ophiolite of Sebuku Island (South Kalimantan, Indonesia) is reported for the first time. Two types of chromitite have been recognized; one with high-Cr composition (Cr/(Cr + Al) > 0.7) occurs in the deep mantle, the other, high-Al (Cr/(Cr + Al) < 0.6), is located close to the Moho transition zone. The TiO2-Al2O3 relations indicate affinity to IAT and MORB, for the high-Cr and high-Al chromitites, respectively. However, both are believed to have formed by mantle/melt reaction and differentiation of a magma characterized by an initial IAT composition related to an SSZ. Primary magmatic inclusions (<10 μm) of laurite characterized by Ru/Os chondritic ratio are the only PGM found in the high-Cr chromitites, indicating crystallization from undifferentiated magma, at low fS2 in the mantle. In contrast, the high-Al to chondrite, suggesting the increase of fS2 in the evolved melt. Besides laurite, the high-Al chromitite contains a complex assemblage of secondary PGM (Pt-Fe, garutiite, iridium, ruthenium–magnetite aggregates, zaccariniite and unnamed Ru and Mn oxides). These secondary PGM have an irregular shape and occur exclusively in the chlorite matrix sometimes associated with Mn-Ni-Fe-Cr hydroxides. They are interpreted to have formed by desulfuration of primary interstitial PGM sulfides or to have precipitated from secondary fluids during low T alteration. The relative abundance of PPGE in the high-Al chromitite is interpreted as a result of PGE fractionation during differentiation of the parent melt of the chromitites. © 2022 by the authors.